MODEL-MODEL HUBUNGAN AGAMA DAN NEGARA - Siagian, Juni Yanti; Karina Berutu, Lolo Ate (Jurnal Ushuluddin, 2024)
This article aims to provide know ledge and insight into the concept of Islam andthe dif erences between religious law and state law according to various expertopinions. The writing method adopted by this article is library research. The typeof data from this method is obtained from data collections or scientific writingwhich has the aim of solving a problem that occurs through critical and in-depthresearch on relevant library data. Data also comes from other research-relatedsources. This paper uses text approach to determine how the model of political thought possessed by Ali Abdurraziq. In addition, it also used the sociological approach to see the extent of originality of Abdurraziq thought. In the map of the contemporary Islamic political thought, especially in the study of the relationshipbetween religion and the state, is found three patterns of thought; secularist,traditionalists and reformers. Based on this pattern, Ali Abdurraziq thought can be categorized as a secularist thought.